ANALYSIS OF THE USE OF RUBBER SANDAL WASTE AS A SUBSTITUTE FOR SOME OF THE COARSE AGGREGATE IN CONCRETE - AMELIA PUTRI SAMANHURI; GALI PRIBADI; GITA PUSPA ARTIANI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2025)
Based on SNI 1974: 2023, concrete is a composite material that hardens over time and has compressive strength at 28 days. Concrete is widely used because of its advantages, despite its disadvantages such as weight, cracking, and high formwork costs. This study reviews rubber sandal waste as a substitute for coarse aggregate at 15% and 30% to reduce the weaknesses of concrete. The background is the growth of industry, particularly the rubber sandal industry, which produces large amounts of waste. The test results show that concrete without waste (0%) achieved a compressive strength of 18.94 MPa (7 days) and 34.74 MPa (14 days), exceeding the SNI 1974: 2023 limit. With a rubber sandal waste composition of 15%, the compressive strength was 16.65 MPa (7 days) and 21.24 MPa (14 days), only meeting the 7-day requirement. The 30% composition showed similar results. This means that the use of rubber sandal waste up to 30% reduces compressive strength performance at 14 days.